Islam, culture and history in the Malay World - Zakariya, Hafiz (Universiti Malaysia Terengganu Press, 2022)
This book traces the influence of Islam on the Malay world. It makes an important contribution to our understanding of how Islam has transformed culture, religion, politics and education of the Malay society.